Homeworking women : - Phizacklea, Annie (Sage Publications, 1995)
An up-to-date overview of all types of home-based work is provided in this volume, which makes an important contribution to sociological and policy debates on homeworking.The authors argue that homeworking replicates wider divisions in the labour force and that its potential for improving women's employment opportunities is therefore limited. Using original research, they outline the advantages and disadvantages, the pay and conditions, and the family situations for contemporary women homeworkers. Gender, class, racism and ethnicity are shown to be key factors in constructing the homeworking labour force.